Low-cost silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
By using cross-linking curing and carbonization processes of nano-silicon and resin prepolymers in the negative electrode materials of lithium-ion batteries, a low-cost "seed-pulp-shell" structure silicon-carbon anode material is formed, and the existing silicon-carbon anode material production is solved. The problems of high cost and high resistivity achieve both high performance and low cost.
Patent Information
- Application Number
- CN202411598885.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing new silicon carbon anode materials have high production process costs and high resistivity, making it difficult to meet the market demand for fast charging performance of lithium batteries.
By mixing nanosilicon and resin prepolymers and cross-linking curing and carbonizing, a low-cost silicon-carbon negative electrode material with a "seed-pulp-shell" structure is formed. The nanosilicon is wrapped with a carbon framework and a carbon coating. Reduce resistivity and improve performance.
It has achieved a gram capacity and first effect comparable to the new silicon carbon negative electrode material, while reducing costs, low powder resistivity, easy industrialization, and good charging and discharge cycle stability.
Smart Images

Figure CN119480981A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and in particular relates to a low-cost silicon-carbon negative electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] After many technical iterations and upgrades, the performance indicators of silicon-based negative electrodes have basically reached the requirements for use. The new generation of silicon-carbon negative electrodes represented by new silicon-carbon have excellent performance in terms of gram capacity, first efficiency, cycle life, etc. However, the production process of this product requires the use of silane gas, which is flammable and explosive, and has extremely high requirements for equipment and relatively high production costs. This is one of the reasons why new silicon-carbon has not been able to be mass-produced. However, the resistivity of pure low-cost silicon-carbon negative electrode materials is relatively high. When applied to lithium batteries, the fast charging performance is difficult to meet market demand. Summary of the invention
[0003] In order to solve the technical problems existing in the background technology, the present invention proposes a low-cost silicon-carbon negative electrode material, a preparation method thereof and a lithium-ion battery. The silicon-carbon negative electrode material not only has the gram capacity and first efficiency and other properties comparable to those of new silicon-carbon, but also has low powder resistivity, low cost and easy industrialization.
[0004] The present invention provides a method for preparing a low-cost silicon-carbon negative electrode material, comprising the following steps:
[0005] S1, mixing nano silicon and resin prepolymer, and then cross-linking, curing and carbonizing to obtain a silicon-carbon precursor;
[0006] S2. After the silicon-carbon precursor is carbon-coated, the silicon-carbon negative electrode material is obtained.
[0007] In the present invention, after nano-silicon and resin prepolymer are mixed and cross-linked and cured, the nano-silicon is wrapped inside the cross-linked resin, and then carbonized and carbon-coated after drying. The resulting silicon-carbon negative electrode material presents a watermelon structure in the form of "seed-pulp-shell", wherein the seed represents nano-silicon, the pulp represents the carbon skeleton, and the shell represents the carbon coating layer. In the silicon-carbon negative electrode material with this structure, the carbon skeleton formed after the resin is carbonized can better inhibit the expansion effect of nano-silicon and prevent the silicon particles from falling off during the charge and discharge cycle.
[0008] Preferably, in step S1, the nano-silicon is nano-silicon with a particle size of 30-150 nm, and the resin prepolymer is a phenolic resin prepolymer and / or a urea-formaldehyde resin prepolymer;
[0009] In the present invention, the nano silicon can be sand-ground silicon or vapor-deposited nano silicon.
[0010] Preferably, the mass ratio of the nano-silicon to the resin prepolymer is 1:1-3.
[0011] Preferably, in step S1, when the nano silicon and the resin prepolymer are mixed, a conductive additive is also added;
[0012] Preferably, the conductive additive is carbon nanotubes and conductive carbon black;
[0013] Preferably, the mass ratio of the carbon nanotubes, the conductive carbon black and the nano-silicon is 0.1-1:0.5-2:100.
[0014] In the present invention, a conductive additive is added when nano silicon and resin prepolymer are mixed. After carbonization, the conductive additive is coated in the carbon skeleton like nano silicon. At this time, the conductive additive can form a conductive network inside the material, thereby effectively reducing the powder resistance of the material and improving the rate performance of the material.
[0015] Preferably, the mixing is achieved by adding the nano-silicon and the resin prepolymer into an alcohol solvent and stirring;
[0016] Preferably, the alcohol solvent is at least one of ethanol, isopropanol, n-butanol, 2-butanol or 1-pentanol;
[0017] Preferably, the stirring rate is 300-800 r / min.
[0018] In the present invention, in a specific implementation, nano silicon can be firstly evenly dispersed in an alcohol solvent to obtain a nano silicon dispersion having a solid content of 10-20wt%, and at the same time, a resin prepolymer is dispersed in an alcohol solvent to obtain a resin dispersion having a solid content of 20-30wt%. By mixing the nano silicon dispersion and the resin dispersion, a gel material mixture is obtained, thereby achieving efficient mixing of the two.
[0019] Preferably, the cross-linking and curing is achieved by adding a cross-linking agent and a catalyst to catalyze the cross-linking reaction;
[0020] Preferably, the cross-linking agent is at least one of formaldehyde, malondialdehyde, succindialdehyde, glutaraldehyde, 2-hydroxyglutaraldehyde or maleic aldehyde, and the catalyst is at least one of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate or sodium bicarbonate;
[0021] Preferably, the mass ratio of the crosslinking agent, the catalyst and the resin prepolymer is 20-50:1-5:100;
[0022] Preferably, the temperature of the catalytic cross-linking reaction is 65-80° C. and the time is 2-6 hours.
[0023] In the present invention, under the action of the cross-linking agent and the alkaline catalyst, the resin prepolymer undergoes a cross-linking and curing reaction, and the three-dimensional skeleton network thus produced can tightly wrap the nano-silicon therein. If a conductive additive is added, the conductive additive can be evenly interspersed in the nano-silicon and the three-dimensional skeleton network to form a conductive network that is connected inside and outside.
[0024] Preferably, in step S1, the carbonization is carried out under an inert gas;
[0025] Preferably, the inert gas is at least one of nitrogen, argon, helium or neon;
[0026] Preferably, the carbonization temperature is 600-1200°C, preferably 800-900°C;
[0027] Preferably, before the carbonization, the cross-linked solidified product is directly spray-dried, or centrifugally separated and then air-dried, and the drying temperature is preferably 60-120°C.
[0028] In the present invention, spray drying or blast drying can prevent the internal skeleton structure of the mixed gel material from being affected by solvent volatilization, thereby ensuring the electrochemical performance of the obtained silicon-carbon negative electrode material after carbonization.
[0029] In step S1, before mixing the nano silicon and the resin prepolymer, the nano silicon is further subjected to aldehyde modification;
[0030] Preferably, the aldehyde modification is obtained by coupling the nano-silicon with an isocyanate silane coupling agent and then condensing it with p-hydroxybenzaldehyde.
[0031] In the present invention, after the nano-silicon and the isocyanate silane coupling agent are coupled to react, the isocyanate group is grafted on the surface of the nano-silicon, which can undergo a condensation reaction with p-hydroxybenzaldehyde to obtain aldehyde-modified nano-silicon. The aldehyde-modified nano-silicon can undergo a cross-linking reaction with a resin prepolymer under subsequent catalyst conditions, so that the obtained cross-linked resin polymer can be tightly combined with the surface of the nano-silicon, and after carbonization, the expansion effect of the nano-silicon can be more effectively suppressed.
[0032] Preferably, in step S2, the carbon coating is formed by chemical vapor deposition of an organic carbon source gas on the surface of the silicon-carbon precursor;
[0033] Preferably, the organic carbon source gas is at least one of acetylene, methane, ethane or propane;
[0034] Preferably, the organic carbon source gas further includes a protective gas, and the protective gas is at least one of nitrogen, argon, helium or neon, and the proportion of the protective gas is preferably 50-85%;
[0035] Preferably, the chemical vapor deposition temperature is 500-750° C. and the time is 2-6 hours.
[0036] The present invention also provides a low-cost silicon-carbon negative electrode material, which is prepared by the above preparation method.
[0037] The present invention also provides a lithium-ion battery, which includes the above-mentioned low-cost silicon-carbon negative electrode material.
[0038] Beneficial effects of the present invention:
[0039] (1) In the present invention, a large amount of nano-silicon is evenly distributed inside the three-dimensional skeleton. The three-dimensional carbon skeleton can well inhibit the expansion effect of nano-silicon. The carbon coating can form stable secondary particles to prevent the silicon particles from falling off during the charge and discharge cycle. Therefore, the obtained silicon-carbon negative electrode material is comparable to the existing silicon-carbon negative electrode material in terms of the reversible capacity ratio and the electrochemical performance of the first charge and discharge efficiency.
[0040] (2) In the present invention, the nano-silicon-conductive aid slurry is mixed with the organic resin solution and then cross-linked and cured to obtain a composite powder, which is then carbonized to achieve secondary coating, thereby forming a low-cost silicon-carbon negative electrode material in the form of a "seed-pulp-shell" structure. The preparation method is simple, the cost is low, and it is easy to industrialize.
[0041] (3) In the present invention, nano-silicon and conductive additives can be better dispersed in the resin system in the solution state, thereby constructing an interconnected internal conductive network, which not only reduces the powder resistance of the negative electrode material, but also effectively improves the rate performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a SEM image of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention;
[0043] Figure 2 This is a cross-sectional SEM image of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention;
[0044] Figure 3 This is a test chart of the charge and discharge specific capacity of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] Example 1
[0046] This embodiment provides a low-cost silicon-carbon negative electrode material, and the specific steps of the preparation method thereof are as follows:
[0047] (1) adding 20 g of nano-silicon (particle size of 40 nm), 0.1 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.2 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing by ultrasonication to obtain a nano-silicon-conductive aid slurry;
[0048] (2) adding 40 g of phenolic resin prepolymer to 150 g of ethanol, stirring at a rate of 500 r / min until the solution becomes clear, then adding 35.2 g of formaldehyde aqueous solution (content of 37 wt %) and 1.2 g of potassium hydroxide powder into the solution, and continuing to stir and mix to obtain a phenolic resin-formaldehyde solution;
[0049] The phenolic resin prepolymer is prepared by the following method: phenol is dispersed in a formaldehyde aqueous solution (content is 37wt%) at a mass ratio of 1:3.5, and then a sodium hydroxide solution (concentration is 0.1mol / L) with a mass 20 times that of phenol is added, and the mixture is stirred at 70°C for 1h and vacuum dehydrated to obtain a phenolic resin prepolymer;
[0050] (3) adding the nano-silicon-conductive aid slurry and phenolic resin-formaldehyde solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature, heating to 70° C., and stirring at a rate of 800 r / min for 3 h to obtain a nano-silicon-phenolic resin gel;
[0051] (4) drying the nano-silicon-phenolic resin gel at 105° C. using a spray dryer with an atomizing disk speed of 20,000 r / min, and carbonizing the resulting dried material at 800° C. for 3 h under a nitrogen atmosphere to obtain a silicon-carbon precursor;
[0052] (5) The silicon-carbon precursor is put into a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is kept at 600°C for 3 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0053] Figure 1 This is a SEM image of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention. Figure 1 It can be seen that the surface of the silicon-carbon negative electrode material contains a small amount of nano-silicon. The surface of the nano-silicon is coated by a carbon coating process to form stable secondary particles, thereby preventing the silicon particles from falling off during the charge and discharge cycle process.
[0054] Figure 2 This is a cross-sectional SEM image of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention. Figure 2 It can be seen that a large amount of nano-silicon is evenly distributed inside the resin carbon skeleton, and the particle size of the nano-silicon particles is 50-80nm.
[0055] Example 2
[0056] This embodiment provides a low-cost silicon-carbon negative electrode material, and the specific steps of the preparation method thereof are as follows:
[0057] (1) adding 20 g of nano-silicon (particle size of 60 nm), 0.02 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.4 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing by ultrasonication to obtain a nano-silicon-conductive aid slurry;
[0058] (2) adding 40 g of phenolic resin prepolymer to 150 g of ethanol, stirring at a rate of 500 r / min until the solution becomes clear, then adding 54.1 g of malondialdehyde aqueous solution (content of 37 wt%) and 2.0 g of sodium hydroxide powder into the solution, and continuing to stir and mix to obtain a phenolic resin-malondialdehyde solution;
[0059] The phenolic resin prepolymer is prepared by the following method: phenol is dispersed in a formaldehyde aqueous solution (content is 37wt%) at a mass ratio of 1:3.5, and then a sodium hydroxide solution (concentration is 0.1mol / L) with a mass 20 times that of phenol is added, and the mixture is stirred at 70°C for 1h and vacuum dehydrated to obtain a phenolic resin prepolymer;
[0060] (3) adding the nano-silicon-conductive aid slurry and the phenolic resin-malondialdehyde solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature, heating to 80° C., and stirring at a rate of 800 r / min for 2 h to obtain a nano-silicon-phenolic resin gel;
[0061] (4) drying the nano-silicon-phenolic resin gel at 105° C. using a spray dryer with an atomizing disk speed of 20,000 r / min, and carbonizing the resulting dried material at 1,200° C. for 2 h under a nitrogen atmosphere to obtain a silicon-carbon precursor;
[0062] (5) The silicon-carbon precursor is put into a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is kept at 500°C for 6 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0063] Example 3
[0064] This embodiment provides a low-cost silicon-carbon negative electrode material, and the specific steps of the preparation method thereof are as follows:
[0065] (1) adding 20 g of nano-silicon (particle size of 40 nm), 0.2 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.1 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing by ultrasonication to obtain a nano-silicon-conductive aid slurry;
[0066] (2) adding 40 g of phenolic resin prepolymer to 150 g of ethanol, stirring at a rate of 500 r / min until the solution becomes clear, then adding 21.6 g of formaldehyde aqueous solution (content of 37 wt%) and 0.4 g of potassium hydroxide powder into the solution, and continuing to stir and mix to obtain a phenolic resin-formaldehyde solution;
[0067] The phenolic resin prepolymer is prepared by the following method: phenol is dispersed in a formaldehyde aqueous solution (content is 37wt%) at a mass ratio of 1:3.5, and then a sodium hydroxide solution (concentration is 0.1mol / L) with a mass 20 times that of phenol is added, and the mixture is stirred at 70°C for 1h and vacuum dehydrated to obtain a phenolic resin prepolymer;
[0068] (3) adding the nano-silicon-conductive aid slurry and phenolic resin-formaldehyde solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature, heating to 65° C., and stirring at a rate of 800 r / min for 6 h to obtain a nano-silicon-phenolic resin gel;
[0069] (4) After filtering the nano-silicon-phenolic resin gel, place it in an 80° C. forced air drying oven and dry it for 6 h. The resulting dried material is carbonized at 600° C. for 5 h under a nitrogen atmosphere to obtain a silicon-carbon precursor.
[0070] (5) The silicon-carbon precursor is placed in a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is carried out at 750°C for 2 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0071] Example 4
[0072] This embodiment provides a low-cost silicon-carbon negative electrode material, and the specific steps of the preparation method thereof are as follows:
[0073] (1) adding 20 g of nano-silicon (particle size of 40 nm), 0.1 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.2 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing by ultrasonication to obtain a nano-silicon-conductive aid slurry;
[0074] (2) adding 40 g of urea-formaldehyde resin prepolymer to 150 g of ethanol, stirring at a rate of 500 r / min until the solution becomes clear, then adding 35.2 g of formaldehyde aqueous solution (content of 37 wt%) and 1.2 g of potassium hydroxide powder into the solution, and continuing to stir and mix until uniform, to obtain a urea-formaldehyde resin-formaldehyde solution;
[0075] The urea-formaldehyde resin prepolymer is prepared by the following method: dispersing urea in a formaldehyde aqueous solution (content of 37 wt%) at a mass ratio of 1:2, adding triethanolamine to adjust the pH value to 9, stirring and reacting at 80° C. for 1 hour, adjusting the pH value to neutral, and vacuum dehydrating to obtain a urea-formaldehyde resin prepolymer;
[0076] (3) adding the nano-silicon-conductive aid slurry and urea-formaldehyde resin-formaldehyde solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature, heating to 70° C., and stirring at a rate of 800 r / min for 3 h to obtain a nano-silicon-urea-formaldehyde resin gel;
[0077] (4) drying the nano-silicon-urea-formaldehyde resin gel at 105° C. using a spray dryer with an atomizing disk speed of 20,000 r / min, and carbonizing the resulting dried material at 800° C. for 3 h under a nitrogen atmosphere to obtain a silicon-carbon precursor;
[0078] (5) The silicon-carbon precursor is put into a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is kept at 600°C for 3 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0079] Example 5
[0080] This embodiment provides a low-cost silicon-carbon negative electrode material, and the specific steps of the preparation method thereof are as follows:
[0081] (1) adding 20 g of aldehyde-modified nano-silicon, 0.1 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.2 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing them by ultrasonication to obtain a nano-silicon-conductive additive slurry;
[0082] The aldehyde-modified nano-silicon is prepared by the following method: dispersing nano-silicon (particle size of 40 nm) in an ethanol aqueous solution (volume ratio of 4:1), dripping ammonia water (concentration of 15wt%), and then adding 3-isocyanate propyl triethoxysilane, the mass ratio of nano-silicon, ammonia water and 3-isocyanate propyl triethoxysilane is 1:0.5:0.05, stirring and reacting at 60° C. for 4 hours, centrifuging, washing with an ethanol aqueous solution until neutral, and drying to obtain isocyanate-modified nano-silicon; adding the isocyanate-modified nano-silicon and p-hydroxybenzaldehyde in a mass ratio of 1:0.01 to toluene, heating to 80° C. and reacting for 3 hours, removing the solvent under reduced pressure to obtain aldehyde-modified nano-silicon;
[0083] (2) adding 40 g of phenolic resin prepolymer to 150 g of ethanol, stirring at a rate of 500 r / min until the solution becomes clear, then adding 35.2 g of formaldehyde aqueous solution (content of 37 wt %) and 1.2 g of potassium hydroxide powder into the solution, and continuing to stir and mix to obtain a phenolic resin-formaldehyde solution;
[0084] The phenolic resin prepolymer is prepared by the following method: phenol is dispersed in a formaldehyde aqueous solution (content is 37wt%) at a mass ratio of 1:3.5, and then a sodium hydroxide solution (concentration is 0.1mol / L) with a mass 20 times that of phenol is added, and the mixture is stirred at 70°C for 1h and vacuum dehydrated to obtain a phenolic resin prepolymer;
[0085] (3) adding the nano-silicon-conductive aid slurry and phenolic resin-formaldehyde solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature, heating to 70° C., and stirring at a rate of 800 r / min for 3 h to obtain a nano-silicon-phenolic resin gel;
[0086] (4) drying the nano-silicon-phenolic resin gel at 105° C. using a spray dryer with an atomizing disk speed of 20,000 r / min, and carbonizing the resulting dried material at 800° C. for 3 h under a nitrogen atmosphere to obtain a silicon-carbon precursor;
[0087] (5) The silicon-carbon precursor is put into a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is kept at 600°C for 3 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0088] Comparative Example 1
[0089] This comparative example proposes a low-cost silicon-carbon negative electrode material, and its preparation method is the same as that of Example 1, except that the addition of carbon nanotubes and conductive carbon black is omitted in step (1).
[0090] Comparative Example 2
[0091] This comparative example proposes a low-cost silicon-carbon negative electrode material, and the specific steps of its preparation method are as follows:
[0092] (1) adding 20 g of nano-silicon (particle size of 40 nm), 0.1 g of carbon nanotubes (single-walled carbon nanotube powder) and 0.2 g of conductive carbon black (Ketjen black) to 180 g of ethanol, and uniformly dispersing by ultrasonication to obtain a nano-silicon-conductive aid slurry;
[0093] (2) adding 40 g of phenolic resin prepolymer to 150 g of ethanol, and stirring at a rate of 500 r / min until the solution becomes clear, to obtain a phenolic resin solution;
[0094] The phenolic resin prepolymer is prepared by the following method: phenol is dispersed in a formaldehyde aqueous solution (content is 37wt%) at a mass ratio of 1:3.5, and then a sodium hydroxide solution (concentration is 0.1mol / L) with a mass 20 times that of phenol is added, and the mixture is stirred at 70°C for 1h and vacuum dehydrated to obtain a phenolic resin prepolymer;
[0095] (3) adding the nano-silicon-conductive aid slurry and the phenolic resin solution into a reaction kettle, stirring at a rate of 500 r / min for 30 min at room temperature to obtain a nano-silicon-phenolic resin gel;
[0096] (4) drying the nano-silicon-phenolic resin gel at 105° C. using a spray dryer with an atomizing disk speed of 20,000 r / min, and carbonizing the resulting dried material at 800° C. for 3 h under a nitrogen atmosphere to obtain a silicon-carbon precursor;
[0097] (5) The silicon-carbon precursor is put into a rotary kiln vapor deposition device, and a mixed gas of acetylene and nitrogen is introduced, with an acetylene flow rate of 60 mL / min and a nitrogen flow rate of 120 mL / min. After the reaction is kept at 600°C for 3 hours, the low-cost silicon-carbon negative electrode material is obtained.
[0098] Comparative Example 3
[0099] This comparative example proposes a silicon-carbon negative electrode material, and the specific preparation method thereof is as follows:
[0100] 1000g of porous carbon was put into a fluidized bed vapor deposition equipment, and a mixed gas of monosilane and nitrogen was introduced with a monosilane flow rate of 3L / min and a nitrogen flow rate of 12L / min. The reaction was kept warm at 540°C for 4h. After the reaction was completed, the equipment was flushed with nitrogen for 30min, and then a mixed gas of acetylene and nitrogen was introduced with an acetylene flow rate of 2L / min and a nitrogen flow rate of 13L / min. The reaction was kept warm at 600°C for 1.5h to obtain the silicon-carbon negative electrode material.
[0101] The silicon-carbon negative electrode material described in the above embodiments and comparative examples is used as the negative electrode material, mixed with a conductive agent (Super-P), a binder sodium carboxymethyl cellulose (CMC) and a polyacrylic acid binder (LA133) in a mass ratio of 80:10:8:2, and an appropriate amount of ultrapure water is added to form a slurry, which is coated on a copper foil, and is vacuum dried and rolled to prepare a negative electrode sheet; a metal lithium sheet is used as the positive electrode, and a 1 mol / L LiPF6 conductive salt and a solvent of DMC:DEC:EC (wt%) = 1:1:1 are used as the electrolyte. A polypropylene microporous membrane is used as the diaphragm, and the above materials are assembled into a CR2025 button battery.
[0102] The charge and discharge test of button cells was carried out on the Blue Power Battery Test System at room temperature with a constant current of 0.1C and a charge and discharge voltage limit of 0.005-1.5V. The results are shown in Table 1 below.
[0103] Table 1 is the electrochemical performance test data of the silicon-carbon negative electrode materials described in the examples and comparative examples
[0104]
[0105]
[0106] It can be seen from Table 1 above that the low-cost silicon-carbon negative electrode material of the present invention has high first reversible specific capacity, good cycle stability, low powder resistivity and good stability.
[0107] In Comparative Example 1, since the conductive aid is omitted, the resistivity parameters of the silicon-carbon negative electrode material are significantly reduced; in Comparative Example 2, compared with Example 1, no cross-linking agent and catalyst are added, and subsequent cross-linking and curing cannot be performed, so the silicon volume inhibition effect in the obtained silicon-carbon negative electrode material is weakened; Comparative Example 3 is a silicon-carbon negative electrode material prepared by existing conventional methods. By comparison, it can be seen that the electrochemical performance parameters of the silicon-carbon negative electrode material of the present invention are comparable to those of existing silicon-carbon negative electrode materials, but the cost is greatly reduced.
[0108] Figure 3 This is a charge and discharge specific capacity test diagram of the low-cost silicon-carbon negative electrode material described in Example 1 of the present invention, Figure 3 It can be seen that the electrochemical indicators such as the reversible capacity ratio and the first charge and discharge efficiency of the low-cost silicon-carbon negative electrode material prepared in Example 1 are at a relatively high level.
[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a low-cost silicon-carbon negative electrode material, characterized in that: The steps include: S1, mixing nano silicon and resin prepolymer, and then cross-linking, curing and carbonizing to obtain a silicon-carbon precursor; S2. After the silicon-carbon precursor is carbon-coated, the silicon-carbon negative electrode material is obtained.
2. The method for preparing a low-cost silicon-carbon negative electrode material according to claim 1, characterized in that: In step S1, the nano-silicon is nano-silicon with a particle size of 30-150 nm, and the resin prepolymer is a phenolic resin prepolymer and / or a urea-formaldehyde resin prepolymer; Preferably, the mass ratio of the nano-silicon to the resin prepolymer is 1:1-3.
3. The method for preparing a low-cost silicon-carbon negative electrode material according to claim 2, characterized in that: In step S1, when the nano silicon and the resin prepolymer are mixed, a conductive additive is also added; Preferably, the conductive additive is carbon nanotubes and conductive carbon black; Preferably, the mass ratio of the carbon nanotubes, the conductive carbon black and the nano-silicon is 0.1-1:0.5-2:
100.
4. The method for preparing a low-cost silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The mixing is achieved by adding nano silicon and resin prepolymer into an alcohol solvent and stirring; Preferably, the alcohol solvent is at least one of ethanol, isopropanol, n-butanol, 2-butanol or 1-pentanol; Preferably, the stirring rate is 300-800 r / min.
5. The method for preparing a low-cost silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The cross-linking curing is achieved by adding a cross-linking agent and a catalyst to catalyze the cross-linking reaction; Preferably, the cross-linking agent is at least one of formaldehyde, malondialdehyde, succindialdehyde, glutaraldehyde, 2-hydroxyglutaraldehyde or maleic aldehyde, and the catalyst is at least one of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate or sodium bicarbonate; Preferably, the mass ratio of the crosslinking agent, the catalyst and the resin prepolymer is 20-50:1-5:100; Preferably, the temperature of the catalytic cross-linking reaction is 65-80° C. and the time is 2-6 hours.
6. The method for preparing a low-cost silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: In step S1, the carbonization is carried out under an inert gas; Preferably, the inert gas is at least one of nitrogen, argon, helium or neon; Preferably, the carbonization temperature is 600-1200°C, preferably 800-900°C; Preferably, before the carbonization, the cross-linked solidified product is directly spray-dried, or centrifugally separated and then air-dried, and the drying temperature is preferably 60-120°C.
7. The method for preparing a low-cost silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: In step S1, before mixing the nano silicon and the resin prepolymer, the nano silicon is further subjected to aldehyde modification; Preferably, the aldehyde modification is obtained by coupling the nano-silicon with an isocyanate silane coupling agent and then condensing it with p-hydroxybenzaldehyde.
8. The method for preparing a low-cost silicon-carbon negative electrode material according to any one of claims 1 to 7, characterized in that: In step S2, the carbon coating is formed by chemical vapor deposition of an organic carbon source gas on the surface of the silicon-carbon precursor; Preferably, the organic carbon source gas is at least one of acetylene, methane, ethane or propane; Preferably, the organic carbon source gas further includes a protective gas, and the protective gas is at least one of nitrogen, argon, helium or neon, and the proportion of the protective gas is preferably 50-85%; Preferably, the chemical vapor deposition temperature is 500-750° C. and the time is 2-6 hours.
9. A low-cost silicon-carbon negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the low-cost silicon-carbon negative electrode material as described in claim 9.
Citation Information
Cited By
Novel silicon-carbon negative electrode material and preparation method thereof
CN120328562A
Preparation method of spherical silicon-carbon composite negative electrode material
CN121839652A